Physical Properties of Yoghurt During Storage at 4ºC (Jurnal Ilmu dan Teknologi Hasil Ternak, 2008)
The purpose of this research was to find out physical properties of yogurt during storage at 4ºC. Yoghurt starters were using Lactobacillus bulgaricus FNCC 0041 and Streptococcus thermophilus FNCC 0040 (1:1). Yoghurt starter was inoculated on 10% (w/v) of skim milk and 10% (w/v) of skim milk which contained 5% (w/v) of sucrose, incubated at 42ºC for 6 hours then storage at 4ºC for 30 days. The result showed that posacidification until 6 days storage, pH tend constant between 6 days and 30 days. Until 9 days texture tend constant, but after 9 days storage texture tend decreasing. Storage yogurt at 10˚C for 12 hours before 4˚C gave higher viscosity, viscosity tend constant until 30 days storage. Water Holding Capacity increasing until 6 days storage, after 6 days tend constant. Sineresis increasing until 6 days storage, after 6 days tend constant. It concluded that physical properties of yogurt gave a little changes on first week storage, after that tend constant until 30 days storage.   Keywords: yogurt, pH, Texture, Viscosity, Water Holding Capacity, Sineresis